Pengembangan Produk Lokal melalui Pendampingan Pembuatan Dodol Sirsak di Desa Puteri Betung, Kabupaten Gayo Lues - Delfia Herwanis; Maria Sanola; Maulida Maulida (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This community service activity aims to explore and optimize the local potential of the abundant soursop fruit in Puteri Betung Village, Gayo Lues Regency. The primary problem lies in the local community's underutilization of the abundant soursop fruit. This activity was conducted in the form of training on making soursop dodol and product packaging design. The methods used include a participatory approach, direct training, and evaluation of the work produced. This activity resulted in an increased understanding among the community regarding the added value of soursop fruit, improved technical skills in product processing, and support from the local government for the continuation of the product. The soursop dodol product successfully won 1st place in the local potential utilization category at the district-level expo. The results of this activity show that local potential-based mentoring can be an effective medium for empowering the community's economy.